STUDY OF INDIVIDUAL’S PRAKRITI AND GENE POLYMORPHISM CORRELATION OF P2Y12 GENE - Shekhar Gopalrao Uike (AYUSHDHARA, 2019)
Ayurveda is a science of self understanding. It is understood by its own unique nature or constitution i.e. Prakruti. Ayurveda believes that the individual’s constitution (Prakruti) is framed at the time of conception as a genetic code or predominant Panchamahabhautic dosha. Ayurveda classifies human beings into three distinct types: Vata, Pitta and Kapha with multiple subtypes. Rakta is said to be the 4th Dosha, i.e. it has the importance as that of Tridosha. All Dhatus are dependent for their nourishment on Raktadhatu. Chakrapani explains different shades of Raktadhatu according to different Prakriti. So there is close relation between Raktadhatu and Prakriti. Doshas which are responsible for Prakriti remain constant and they do not change until death. Genetic constitution is identical and unique for every person, the same as Prakriti. Every gene performs a specific function. So Prakriti can be correlated with genetics whether there is any particular genetic pattern for the particular Prakriti with the help of a tool like Single Nucleotide Polymorphism. P2Y12, the receptor present on the platelet surface, initiates platelet aggregation. To analyse polymorphism in the P2Y12 gene, in exhibiting platelet aggregative response, in correlation with Prakriti.